The Impact of Online Interactions on Mental Health among Adolescents in West Java - Tamaulina Br Sembiring; Sabil Mokodenseho (The Eastasouth Journal of Social Science and Humanities, 2023)
Using a quantitative methodology, this study explores the complex relationship between teenage psychological wellness and digital social networking in West Java. A varied group of 250 teenagers took part, offering insights on their use of digital devices and mental well-being. The study identifies complex relationships between online experiences and psychological wellbeing, emphasizing both positive and negative correlations. The results highlight the importance of context-specific knowledge, given the diversity of West Java's culture and population. With implications for theory, practice, and future research, the study adds to the expanding body of knowledge regarding the effects of digital social networking on the mental health of adolescents.